Mockbuster na produção cinematográfica: a imitação é a forma mais sincera de elogio? - Lionço, Bruna (My University, 2019)
The main focus of this study is to identify the way in which the mockbusters are inserted in the cinematographic industry, as well as to verify its technical features in order to increase the knowledge about this practice, which is little discussed in academic research area. Briefly, mockbusters can be described as productions that mimic essential elements of high-profile films in order to promote themselves. This work is structured in two parts: the first seeks bibliographical information that elucidates questions about the insertion of the pattern of imitation within the cinema production field; the second part uses the case study with the support of film analysis to identify the essential elements that characterize the practice of mockbusters films (sic).
O foco principal deste estudo é identificar o modo com que os mockbusters são inseridos na indústria cinematográfica, assim como, verificar quais são suas características, a fim de ampliar os conhecimentos a respeito desta prática, que é pouco abordada em pesquisas acadêmicas. De maneira breve, os mockbusters podem ser descritos como produções que imitam elementos essenciais de filmes de grande repercussão para se promover. O trabalho se estrutura em duas etapas: a primeira busca informações bibliográficas que elucidem questões a respeito da inserção do padrão de imitação dentro da produção de cinema mundial; a segunda parte, utiliza o estudo de caso apoiado pela análise fílmica para identificar os elementos essenciais que caracterizam a prática dos filmes mockbusters (sic).
Keywords: Publicidade; Indústria cinematográfica; Imitação